Woman Exploitation in Warkop DKI Poster Film - Patria, Asidigisianti Surya; Kristiana , Nova; Aryanto, Hendro (Bina Nusantara University, 2021)
The research aimed to determine a representation of women in the poster of Warkop DKI comedy film (Dono, Kasino, Indro) in 1980-1989 from a woman point of view. The involvement of women as models in the film poster media was not yet clear in terms of their roles; however, women could be used more as commodities of capitalism to reap profits. In the patriarchal rule, men were assumed to be created as culture-making in the other women were subordinated. The research applied a descriptive qualitative methods by collecting data using documentation techniques. The collected data was reducted, presented, and concluded. Roland Barthes’ semiotic theory was used to analyze poster design elements that contained the exploitation of the female body. The research results find that (1) women in the film poster media are only subordinated to the poster to attract men, potential viewers. (2) Film posters show sexual exploitation and eroticism that is made into a high-selling and quite promising commodification.